Kriminalisasi Terhadap Kejahatan Carding Sebagai Bentuk Cyber Crime dalam Hukum Pidana Indonesia - I Gede Krisna Ginara; I Made Minggu Widyantara; Ni Komang Arini Styawati (Jurnal Preferensi Hukum, 2022)
Criminalization is an action that was not initially considered a criminal event, then classified as a criminal event for the community. In the era of globalization as now, there are so many cyber crimes that have arisen in Indonesia, cyber crime is an illegal act committed by criminals by utilizing technology and computer network information systems. One thing that happened in Indonesia and is relatively common in society is the crime of carding in the form of evil deeds in using internet technology as a tool in illegally opening a system on a website to obtain credit card information owned by customers. The purposes of this study are to reveal the criminalization of carding crimes in Indonesian criminal law and efforts to overcome carding crimes. This type of research uses a normative legal research type with a statutory and conceptual approach. The data collection technique was carried out using library techniques. The sources of law used are primary, secondary, and tertiary laws. After the data was collected, it was then analyzed qualitatively and presented in a descriptive form. The results of the study reveal that the crime of carding is regulated in Law number 19 of 2016 concerning Amendments to Law number 11 of 2008 concerning Information and Electronic Transactions, and is also formulated in Articles 362, 363 and 378 of the Criminal Code, namely regarding theft and fraud. As for the legal efforts that can be done to prevent carding crimes, they can use repressive and preventive measures.